Finding the Truth Behind the Language - Muji Muji (Pancaran Pendidikan, 2019)
Finding the truth of the behavior expressed through language is not easy. It is due to the meaningless expression that the speaker tends to use. It often appears irrelevant as the first intention was A, but the meaning then referred to B, C, D or even E. Both spoken and written languages sometimes do not reflect the actions being done as in a debate, interview, advertisement, and poster, the content does not match what the speaker tried to deliver. In other words, the meaning expressed or written is uncertain. Through the phenomenological research, it is found to be a problematic language. Through the act of understanding the meaning and its connection to people in certain situations, they could try to express a variety of languages. Through the observation, interview and documentation, the data were found as (1) "Although this movie was produced based on a request, G30S / PKI betrayal film is not cheap work. The film has a structured dramatism that combined the documentary and theatrical aspects. "(2)" Unrevealing the G30S / PKI Film Controversy in 1965, and 3 Eternal Facts "(3)" Which means that every person is able to talk about the 1965 incident and to make their own version of the story,” said Seno. The word “order”, “controversy” and “version” indicated as formal markers that those statements pointed to the G30S / PKI film which is doubted in terms of its value (thematic domain Spradley's term). The data analysis in which strengthened by the language functions can be used to hide certain behaviors that someone did. In this context, the search for the ultimate truth hidden behind the language is not sufficiently supported by oral, written, and drawing/photograph, but it is important to have people who were as the perpetrators, witnesses, or victims’ family. This statement is also considered as criticism and suggestion to avoid bias appeared in the language.